Familicide in Canada, 2010 to 2019 - Boyd, Ciara (Homicide studies, 2024)
Familicide is rare; however, the high victim counts in each incident and context surrounding these killings underscore the need for further research. The purpose of this study is to gain a better understanding of the circumstances surrounding familicide in Canada. Using univariate statistics, this study analyzed 26 incidents of familicide that occurred in Canada between 2010 and 2019. The results show that familicide is a gendered crime involving primarily male accused who often target female victims, have a history of domestic violence, and commit the killings using firearms. This research highlights the importance of developing risk assessment, risk management, and safety planning strategies to address warning signs and prevent future familicides.